4+4+4 Yapısal Değişikliğin Birleştirilmiş Sınıflı Okullara Yansıması ve Öğretmenlerin Beklentileri - Öcal, Sabahat; Elma, Cevat; Yazıcı, Levent; Zabun, Engin; Yıldırım, Nail (Fırat University, 2016)
Birleştirilmiş sınıf uygulaması eğitim sistemimizde zorunlu bir uygulama gibi görünse de beraberinde birçok sorunu da gündeme getirmektedir. Sistemdeki değişiklikler de farklı problemleri beraberinde getirmektedir. 2012-2013 öğretim yılından itibaren eğitim siteminde gerçekleştirilen 4+4+4 yapısal değişikliğin birçok sorunu uygulamaya taşıdığı düşünülmektedir. Yapılan bu çalışmanın amacı birleştirilmiş sınıflı okullarda görev yapan öğretmenlerin 4+4+4 eğitim uygulamasının birleştirilmiş sınıflara yansıması ve okullarının işleyişi ile ilgili görüşlerini almaktır. Ayrıca birleştirilmiş sınıf okutan öğretmenlerin yaşamış oldukları sorunlar, Milli Eğitim Müdürlükleri ve Bakanlıktan beklentileri de ortaya konmak istenmiştir. Çalışma, nitel araştırma yaklaşımı doğrultusunda tasarlanmış olup; “içerik analizi” yapılmış ve olgubilim (fenemenoloji) deseni kullanılmıştır. Araştırmanın çalışma grubunu birleştirilmiş sınıflı okullarda görev yapan 152 öğretmen oluşturmaktadır. Araştırma bulgularına göre 4+4+4 yapısal değişikliği birleştirilmiş sınıflı okullardaki öğretmenleri olumlu ve olumsuz etkilediği görülmektedir.

Although multi-grade classrooms seem to be compulsory in our education system, it has also brought forward several problems. Changes in the system also risen up different problems. It is considered that the structural change of 4+4+4 in education system has brought many problems practically since 2012-2013 school year. The purpose of this study is to get views from the teachers who are serving at schools with multi-age classrooms about the reflection of the application of 4+4+4 education to multi-age classrooms and about the function of schools. Moreover, it is wanted to put forward that the problems of teachers who are teaching at multi-age classrooms and the expectations from Directorates of National Education and Ministiry. The study is designed in the direction of qualitative research approach;furthermore,content analysis is implemented and the pattern of phonemonology is employed.The research group consists of 152 teachers who are working at multi-age classrooms. According to the findings, it is observed that structural change of 4+4+4 affected the teachers who are serving at these schools in a positive and negative way. It is understood that probably the most encountered problems are: working at the same class with&without teachers;lack of funds;overwork for teachers about being a teacher and administrator simultenously;heating problem and indifference of parents to students; physical incapability.
The Reflection of 4+4+4 Structural Change on Multi-Grade Classrooms and Teacher Expectations